UTILITY OF SHORT FORMS OF THE ESCALA DE INTELIGENCIA DE WECHSLER PARA ADULTOS (EIWA) - López López, María José; Rodríguez González, José Manuel; Santín Vilariño, Carmen; Torrico Linares, Esperanza (Anales de Psicología / Annals of Psychology, 2003)
Several short forms of the WAIS are used nowadays as alternative to the application of the complete scale in the estimate of the intellectual capacity. Two are the procedures used for the abbreviation of this instrument, the subtests reduction and items reduced proposed by Satz and Mogel. In this study it is evaluated the effectiveness of both procedures comparatively in the assessment of the intellectual capacity in two groups of subjects, one composed by 184 healthy people and a mixed clinical sample formed by 96 diagnosed psychiatric patients of diverse psychopathologys. The results indicate that the procedure of subtests reduction estimates in a more appropriate way the CI obtained with the application of the complete scale.